Sex and maturity determination of Persian Sturgeon by using ultrasonography methods - M. moghim (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2000)
Sex and maturity determination of live fishes without external sexual dimorphism or when there is no developed external characters is very important from different species. In this regard, the ultrasonography methods was used to determine sex and maturity of Persian sturgeon (Acipenser persicus). 142 collected samples of live fishes of this species (with an age range of 13-20 years) from Caspian Sea were preserved in water tanks and scanned under 5.0 and 7.5 MHZ linear pie medical transducer. Frontal view of right or left lateral side of each fish between pectoral and anal fins were obtained echogenicity and morphologic ultrasonographic findings were studied for evaluating the difference between testis and ovary and their maturity Status. The results obtained from ultrasonography were confirmed by further necropsy examinations. The ultrasonographic accuracy for sex and maturity determination were 100% and 98.6%, respectively. It can be recommended this method can be used with an accurate method to determine sex and maturity of Persian Sturgeon.